PENGEMBANGAN NILAI KARAKTER PESERTA DIDIK DENGAN IMPLEMENTASI PERILAKU SOPAN SANTUN DI SEKOLAH DASAR - Ria Indrawati; Arri Handayani; Dini Rahmawati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This article aims to describe the development of the character of manners in elementary schools, describe solutions in overcoming these obstacles, and describe the efforts of classroom teachers in shaping the character of manners of students in elementary schools. This article uses a descriptive qualitative approach of literature study type. The results of this study are; 1) The efforts made by elementary school class teachers, in the formation of polite character are giving understanding to always respect elders, not saying dirty, rude, and arrogant and greeting the teacher. 2) obstacles faced by teachers in character building are lack of self-confidence in students, lack of attention from parents and teachers must be patient in dealing with students 3) The solution carried out by high-class teachers is to teach children with love and attention because as a teacher it is natural to be a good role model for students.